Comparative study on semen characteristics of Kolbroek and Large White boars following computer aided sperm analysis® (CASA) - Matshidiso Bailekae Masenya; M. L. Mphaphathi; M. H. Mapeka; P. H. Munya; M. B. Makhafola; F. V. Ramukhithi; P. P. Malusi; D. O. Umesiobi; T. L. Nedambale (African Journal of Pig Farming, 2013)
Consistent estimates of boar fertility potential from objective semen evaluation could be a valuable tool for boar selection. The objective of this study was to evaluate semen characteristics of Kolbroek and Large White boars following computer aided sperm analysis® (CASA). Eight ejaculates were collected separately from individual Kolbroek (n = 4) and Large White (n = 4) boars using the gloved-hand technique. Following semen collection, semen was evaluated for macroscopic and microscopic characteristics. Analysis of variance (ANOVA) was used to test the differences between the breeds (P<0.05) . The bodyweight of Kolbroek (154.7 ± 8.5) was significantly lower compared to Large White (189.9 ± 7.7) boar. There was also a positive correlation between bodyweight and semen volume of both Kolbroek (r = 0.2197) and Large White (r = 0.2577) boar. However, no significant differences were observed in Kolbroek and Large White boar semen volume (140 and 170 ml), sperm concentration (0.727 and 0.761 × 109 sperm cell/ml), pH (7.0 and 7.0), total motility (95 and 91%) and morphology (84 and 82%). In conclusion, the bodyweight of Kolbroek and Large White boar was positively correlated with ejaculated semen volume. Sperm characteristics of both Kolbroek and Large White boar were similar. Sperm class analyser® provided a precise and more objective information of sperm motility characteristics